2020
DOI: 10.32615/ps.2019.140
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic activity of common buckwheat (Fagopyrum esculentum Moench) exposed to thermal stress

Abstract: The aim of the work was to investigate thermal stress effect on photosynthetic activity of common buckwheat. Seedlings of common buckwheat were exposed to 20°C (control) and 30°C (thermal stress). The research involved the Polish cultivar 'Panda' and strain PA15 and determined kinetics of chlorophyll a fluorescence (Chlf), leaf gas exchange, soluble carbohydrate (SC) content in donor leaves, electrolyte leakage as a parameter of cell membrane permeability, and amount of abscisic acid and jasmonates. In 'Panda'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The rate of embryo abortion depends on the genotype. Among the studied accessions, we observed significant differences in the percentage of incorrectly developed ovules, both under control conditions and under thermal and nutrient stresses 14 , 22 , 33 , 34 .…”
Section: Discussionmentioning
confidence: 92%
“…The rate of embryo abortion depends on the genotype. Among the studied accessions, we observed significant differences in the percentage of incorrectly developed ovules, both under control conditions and under thermal and nutrient stresses 14 , 22 , 33 , 34 .…”
Section: Discussionmentioning
confidence: 92%
“…Panda is more sensitive to heat stress than PA15 is, as manifested by the degeneration of a large number of embryo sacs [ 9 ]. The plant growth conditions in the phytotron have been described in our previous papers [ 8 , 9 ]. Plants were cultivated in plastic pots of 10 dm 3 capacity (six plants per pot) filled with a mixture of commercial soil substrate (pH = 5.8) and perlite (1:1, v:v ) under a 16 h photoperiod and 300 µmol m −2 s −1 (High-Pressure Sodium, HPS lamps, SON-T+ AGRO, Philips, Brussels, Belgium) at a humidity of 50–60%.…”
Section: Methodsmentioning
confidence: 99%
“…In earlier investigations, we found that buckwheat plants at the vegetative phase develop much better at a higher temperature (30 °C) than at 20 °C [ 8 ]. However, 30 °C is too warm for optimal embryo development [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…That disturbed ongoing experiments. However, the plants sown and grown to the cotyledon stage under solar light supplemented with HPS developed properly throughout further vegetative and generative stages 28 . The plants under both treatments grew at 25 + 2 °C/22 ± 2 °C day/night, with 55–60% humidity and under a 16 h photoperiod.…”
Section: Introductionmentioning
confidence: 98%